Desain Sistem Computer Assisted Test (CAT) Pada Olimpiade Sains Nasional (OSN) Tingkat Provinsi Lampung Berbasis Website dengan Metode SCRUM - Melda Agarina; Arman Suryadi K; Sutedi Sutedi; Muh Royan Fauzi M; Hendri Purnomo; Reyhandoni (Bulletin of Computer Science Research, 2025)
The National Science Olympiad (OSN) is a prestigious competition that requires an accurate, efficient, and transparent assessment system. This study aims to design and develop a web-based Computer Assisted Test (CAT) system for the implementation of OSN at the provincial level in Lampung. The system was developed using the Scrum method, an iterative and incremental software development framework consisting of sprint planning, daily scrum, sprint review, and sprint retrospective stages. The development team consisted of a Scrum Master, Product Owner, and developers, with structured backlog planning and evaluation in each sprint. The CAT system includes features such as question creation, test time configuration, question randomization, automatic scoring, and test result analysis. Testing results indicate that the system meets user needs, enhances assessment efficiency and objectivity, and provides ease of use for participants. This system can be implemented in provincial-level OSN events and serves as an innovative solution to support technology-based assessment systems.